The characteristics of thoracic aortic dissection in autopsy-diagnosed individuals: An autopsy study - Zhao, Qianhao; Yin, Kun; Zhou, Nan; Wu, Qiuping; Xiao, Yuxi; Zheng, Jinxiang; Zheng, Da; Bi, Qiming; Quan, Li; Hu, Bingjie; Cheng, Jianding (Frontiers in Cardiovascular Medicine, 2022)
Thoracic aortic dissection (TAD) is the most common cause of sudden cardiac death associated with aortic diseases. The age of TAD victims in forensic studies is significantly younger than hospitalized patients with TAD, while only a few studies have been conducted on autopsy-diagnosed TAD deceased. A retrospective study was conducted at the Medicolegal Center of Sun Yat-sen University from 1999 to 2019 to address the characteristics of TAD victims. A total of 200 deceased from spontaneous rupture of TAD were assessed, with 165 (82.5%) males and 175 (87.5%) Stanford type A deceased. Our main results showed that compared with patients with TAD diagnosed during their lifetime, individuals diagnosed with TAD until an autopsy showed an earlier onset (43.80 years old) and less accompanied hypertension (<50%). Sudden death was the initial symptom of 32 decedents. Instead of chest/back pain (40 decedents), abdominal pain (59 decedents) was the most common initial symptom, and 42 decedents presented with no accompanying pain. A higher proportion of abdominal pain and the painless symptom was associated with a higher risk of misdiagnosis. Women showed a more atypical clinical presentation and rapid progression than men. Younger decedents showed more pronounced left heart changes. The present study implicated the TAD individuals diagnosed until an autopsy as a particular entity, indicating the urgent need for further investigation on early diagnosis and pathogenesis of patients with TAD with atypical pain and painless or with younger age to reduce the burden of TAD-related sudden death.